2021
DOI: 10.1186/s12955-021-01776-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sleep duration, physical activity, and screen time on health-related quality of life in children and adolescents

Abstract: Background Existing studies on health-related quality of life (HRQoL) mainly covered single growth stages of childhood or adolescence and did not report on the trends in the relationships of HRQoL with sleep duration, physical activity, and screen time. This study aimed to establish the population norm of HRQoL in children and adolescents aged 6–17 years and examine the associations of screen time, sleep duration, and physical activity with HRQoL in this population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
3
18
0
2
Order By: Relevance
“…The grade D was assigned based on six data sources, with four studies having data collected before the COVID-19 outbreak including one old data source 16 , 30 , 31 , 32 and two during the pandemic. 24 , 33 Although increased screen time has been commonly reported among children and adolescents during COVID-19 related lockdowns, 4 not much difference was found in the proportions of children and adolescents meeting the recommendations of no more than 2 h of recreational screen time per day in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…The grade D was assigned based on six data sources, with four studies having data collected before the COVID-19 outbreak including one old data source 16 , 30 , 31 , 32 and two during the pandemic. 24 , 33 Although increased screen time has been commonly reported among children and adolescents during COVID-19 related lockdowns, 4 not much difference was found in the proportions of children and adolescents meeting the recommendations of no more than 2 h of recreational screen time per day in Hong Kong.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al demonstrated that children and adolescents with longer screen time appeared to have a poorer health-related quality of life. 53 Prolonged use of digital devices has also been associated with other adverse health outcomes such as obesity, 54 myopia, 55 , 56 inattention, 57 and mental distress. 58 Our study showed that using digital devices for more than 3 hours per day significantly increased the likelihood of gaming addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Both the Y-3L and the PedsQL were used in children with acute Thalassemia with acceptable reliability on Cronbach's alpha but no comparison of performance between the two measures was made [46]. Similarly, the EQ-5D-Y-5L and PedsQL both showed a decrement in HRQoL with sleep deprivation, physical activity and screen time in a large general population sample in Hong Kong but no comparison between instrument performance was made [47].…”
Section: Discussionmentioning
confidence: 99%